Komparatystyczne ujęcie pojęć „wizerunek”, „utrwalanie” i „rozpowszechnianie” w ujęciu art. 23 k.c., art. 81 ust. 1 pr. aut. oraz art. 191a k.k. - Witczak, Karolina (Filozofia Publiczna i Edukacja Demokratyczna, 2017)
The terms „image”, „recording” and „dissemination” are presented in art. 191a of the Criminal Code. However, the source of these phrases derives from civil law, especially art. 23 of Civil Code and art. 81 of Act of 4 February 1994 on Copyright and Related Rights. The article author makes a comparison of these terms in view of different legal orders (criminal law order and civil law order). The purpose of such a comparative study is to show differences and similarities in the range of designatums of analyzed terms. Furthermore, this article indicates “the most effective” structure of analyzed expressions on the grounds of law in action.